2017
DOI: 10.20473/j.djmkg.v50.i1.p6-9
|View full text |Cite
|
Sign up to set email alerts
|

The cleanliness differences of root canal walls after irrigated with East Java propolis extract and sodium hypoclorite solutions

Abstract: Group 1, 2 and 3 (p<0.05). Based on the Median Control test, the value of 8% East Java propolis extracts was 1,000, which was the best value compared to 2.5% NaOCl, 5% NaOCl and aquadest. Conclusion: It can be concluded that 8% East Java propolis extract is the most effective solution for cleaning root canal walls compared with 2.5% NaOCl and 5% NaOCl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Root canal cleanliness constitutes one of the parameters for effective root canal treatment since research has shown that the smear layer on the root canal walls covers the dentinal tubules. A smear layer constitutes a mixture of organic and inorganic particles that can accumulate during the preparation process relating to the root canal walls 8 and whose cleanliness is observable under SEM, thereby enabling calculation of the number of clean and unclogged dentinal tubules. 11,12 A significant body of recent research has been undertaken into the natural ingredient phytomedicine because of its advantages when compared to the chemical agents currently widely employed within the field of dentistry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Root canal cleanliness constitutes one of the parameters for effective root canal treatment since research has shown that the smear layer on the root canal walls covers the dentinal tubules. A smear layer constitutes a mixture of organic and inorganic particles that can accumulate during the preparation process relating to the root canal walls 8 and whose cleanliness is observable under SEM, thereby enabling calculation of the number of clean and unclogged dentinal tubules. 11,12 A significant body of recent research has been undertaken into the natural ingredient phytomedicine because of its advantages when compared to the chemical agents currently widely employed within the field of dentistry.…”
Section: Discussionmentioning
confidence: 99%
“…7 At a concentration of 8%, propolis is more effective at cleaning the root canal walls of smear layer compared to 2.5% NaOCl. 8 In addition to propolis, another natural ingredient whose use is rapidly gaining in popularity is cocoa pod husk extract (Theobroma cacao) which contains in excess of 500 different chemicals and has traditionally been used as an antioxidant, anticarcinogenic, immunomodulator, vasodilator, antimicrobial, and analgesic. 9 Cocoa pod husk extract can impede the formation of Enterococcus faecalis (E. faecalis) bacterial biofilm at a minimum biofilm inhibitory concentration (MBIC) of 3.12% and possesses significant potential as an alternative root canal irrigation agent.…”
Section: Dental Journal (Majalah Kedokteran Gigi)mentioning
confidence: 99%
“…It was then diluted with aquadest. 12 In this research, 16 samples were split into three treatment groups and one control group. Each group received four test tubes containing 0.875 ml of 0.25 M sucrose in pH 7, 0.2 M phosphate buffer, and 0.1 ml of GTF enzyme solution.…”
Section: Methodsmentioning
confidence: 99%
“…11 Indonesia is considered to have a diverse range of local bee species, including the honey bee or Apis mellifera that produce most of Indonesia's propolis. 12 The properties of propolis compounds depend on the polyphenol and content of polyphenols, both of which are influenced by seasonal factors, local vegetation, place of origin, bee species and the condition of propolis in either fresh or preserved form. 13 Propolis is made up of resin and balsam (50-70%), wax and essential oils (30-50%), pollen (5-10%), and other components such as minerals, amino acids, vitamins A, B complex, E and biochemically active ingredients including bioflavonoids (vitamin P), phenols, and aromatic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…8 Ideally, irrigants have antibacterial properties, the ability to dissolve necrotic tissue, and have a low level of toxicity. 9 Seventeen percent of EDTA solution can soften root canal dentin because it can dissolve the inorganic components of the smear layer. 10 In contrast to NaOCL, which has a broad spectrum of the antibacterial activities, 17% EDTA has lower antibacterial power.…”
Section: Introductionmentioning
confidence: 99%